Peran Anggota Kepolisian Dalmas Polda Bali dalam Penegakan Hukum terhadap Penanganan Unjuk Rasa Tolak Reklamasi Teluk Benoa - I Kadek Windi Pranata Putra; Ida Ayu Putu Widiati; I Nyoman Gede Sugiartha (Jurnal Konstruksi Hukum, 2020)
Every citizen has the right to express an opinion in accordance with Law Number 9 of 1998 concerning Freedom of Expressing Opinions in Public. Freedom of opinion is generally carried out by demonstrations. The recent demonstration in Bali is a demonstration against the reclamation of Benoa Bay. This is of particular concern to members of the Bali Police Dalmas as the main party in the handling of this demonstration. In handling it, the Bali Police Dalmas is guided to enforce the law against each of these demonstrations. Based on this background, this research was conducted with the aim of describing how the role of members of the Bali Police Dalmas police in law enforcement against the Benoa Bay protest against the Benoa Bay reclamation and what factors hindered the implementation of handling the Benoa Bay reclamation protest action by members of the Bali Police Dalmas. This study used an empirical legal research method. The results of this study indicated that the role of the Bali Police Dalmas in enforcing the law against the protest against Benoa Bay reclamation was carried out based on pre-emptive, preventive, and repressive actions based on statutory regulations and the police chief regulations regarding the handling of demonstrations. In addition, the factors that hindered the implementation of the protest against the reclamation of Benoa Bay by members of the Bali Police Dalmas include internal and external factors. the internal factor is factor of Dalmas members themselves, both from a mental perspective, professionalism, and knowledge about how to handle protests. Meanwhile, the external factor is generally the mass of protesters who do not understand the provisions that apply to the implementation of a demonstration.